1994
DOI: 10.1063/1.111486
|View full text |Cite
|
Sign up to set email alerts
|

Growth of 2H-SiC on 6H-SiC by pulsed laser ablation

Abstract: A 2H-SiC thin film has been grown on a 6H-SiC substrate by laser ablation using an excimer laser. The deposition of 2H-SiC film occurred in a high vacuum system (≊10−6 Torr) with the substrate temperature near 1200 °C. Plan-view and cross-sectional transmission electron microscopy (TEM) were used to measure the lattice parameters and to identify the polytype. Cross-sectional TEM images clearly show the symmetry of the film as c-axis oriented 2H-SiC containing columnar grains with an average diameter of 20 nm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Although there were many reports on the synthesis of the 3C-, 4H-and 6H-SiC polytypes, relatively few dealt with the synthesis of 2H-SiC [7][8][9][10]. This is because, the free energy between different polytypes is so small that the 2H-SiC is easily transformed to other polytypes of SiC and thus difficult to form [11].…”
Section: Introductionmentioning
confidence: 93%
“…Although there were many reports on the synthesis of the 3C-, 4H-and 6H-SiC polytypes, relatively few dealt with the synthesis of 2H-SiC [7][8][9][10]. This is because, the free energy between different polytypes is so small that the 2H-SiC is easily transformed to other polytypes of SiC and thus difficult to form [11].…”
Section: Introductionmentioning
confidence: 93%
“…However, SiC quantum dots obtained by etching hexagonal SiC (6H-SiC) have yielded contradictory results on quantum confinement effects [11,12]. The observation of the quantum effects makes SiC nanostructures an even more interesting system because it suggests a possibility of designing SiC based materials with blue or higher frequency emission, e.g., UV.A wurtzite type SiC nanorod with an average diameter of 20 nm and a length of 100 nm has been obtained by pulsed laser ablation on 6H-SiC near 1200 °C [13]. Based on the known stability of the unreconstructed (1010) surface of the wurtzite structure [14], one expects that wurtzite type SiC nanorods (W-SiCNRs) or nanowires (W-SiCNWs) might show remarkable stability.…”
mentioning
confidence: 98%
“…A thick 2H-SiC was grown on 4H-SiC by vapor-liquid-solid process in Si-Li solution, [5] and a thin 2H-SiC was grown on 6H-SiC by pulsed laser ablation. [6] However, the growth is laboring under the high cost and small size of 6H or 4H-SiC substrates. Kusumori et al have also reported 2H-SiC grown on sapphire of an area of 5 × 10 mm 2 by pulsed-laser deposition (PLD).…”
Section: Introductionmentioning
confidence: 99%